Sensor replacement using mobile robots - Ng, Nicholas Thomas. (2009)
Sensor networks is widely known and used in many areas especially in highly dangerous areas. The focus of this final year project is to study on the 3 algorithms: Centralized, Fixed Distributed and Dynamic Distributed Algorithms proposed by Yongguo Mei, Changjiu Xian, Saumitra Das, Y. Charlie Hu and Yung – Hsiang Lu [1]. A simulation program is written out to study the performance of these algorithms. Message and Motion overhead parameters are used to determine the algorithms’ performance. Further improvements such as Depth First Search function were implemented to enhance the performance of the algorithms. Finally to conclude this project, future works such as Geographic Routing Protocol could be implemented to improve the accuracy of these algorithms.